2018
DOI: 10.1111/nph.15269
|View full text |Cite
|
Sign up to set email alerts
|

Understanding genomic diversity in Pseudomonas syringae throughout the forest and on the trees

Abstract: This article is a Commentary on Hulin et al., 219: 672–696.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Genomics-based methods offer unprecedented resolution to analyze strain diversity and evolutionary relationships within the P. syringae complex, besides identifying candidate genes involved in pathogenicity and host range definition ( Lindeberg et al., 2009 ; Baltrus et al., 2011 ; Bartoli et al., 2015 ; Monteil et al., 2016 ; Baltrus et al., 2017 ; Dillon et al., 2019a ; Dillon et al., 2019b ). However, understanding the biological meaning of the observed genomic differences depends on the availability of experimental data confirming specific phenotypes, such as virulence and host range ( Baltrus and Orth, 2018 ). Specifically, testing more than one hundred P. syringae strains on different hosts showed that the host range is an overlapping continuum, with closely related strains exhibiting from extremely narrow to very broad host ranges ( Morris et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genomics-based methods offer unprecedented resolution to analyze strain diversity and evolutionary relationships within the P. syringae complex, besides identifying candidate genes involved in pathogenicity and host range definition ( Lindeberg et al., 2009 ; Baltrus et al., 2011 ; Bartoli et al., 2015 ; Monteil et al., 2016 ; Baltrus et al., 2017 ; Dillon et al., 2019a ; Dillon et al., 2019b ). However, understanding the biological meaning of the observed genomic differences depends on the availability of experimental data confirming specific phenotypes, such as virulence and host range ( Baltrus and Orth, 2018 ). Specifically, testing more than one hundred P. syringae strains on different hosts showed that the host range is an overlapping continuum, with closely related strains exhibiting from extremely narrow to very broad host ranges ( Morris et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from these experiments are not necessarily applicable to perennial species. Plant defense mechanisms can be highly species‐specific, and also pathovars of Ps and perhaps even different strains from the same pathovar can differ in virulence factors and pathogenicity mechanisms (Baltrus & Orth, 2018; Hulin et al., 2020; Preston, 2000; Ruinelli et al., 2019). ‐Few plant nutritionists specialize in fruit tree nutrition, and even fewer work on interactions between plant nutrients and pathogen susceptibility.…”
Section: Introductionmentioning
confidence: 99%